CRISIS MANAGEMENT AND INCIDENT RESPONSE: A NATIONAL DATA CENTER CASE STUDY - Said Ma’ruf (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research aims to analyze crisis management and incident response related to the collapse of the National Data Center (PDN). Through these case studies, the research explores the steps taken by authorities to address the crisis, identifies the challenges faced, and evaluates the effectiveness of the incident response. Data was collected from secondary sources, including official reports, news articles, and interviews with cybersecurity experts. The results showed that despite rapid efforts to contain the incident, there were several weaknesses in preparedness and coordination that needed to be corrected to reduce future risks